Pseudomonas aeruginosa KUCd1, a possible candidate for cadmium bioremediation - Sinha,Sangram (2009)
A cadmium (8 mM) resistant Pseudomonas aeruginosa strain KUCd1 exhibiting high Cd accumulation under in vitro aerobic condition has been reported. The isolate showed a significant ability to remove more than 75% and 89% of the soluble cadmium during the active growth phase from the growth medium and from Cd-amended industrial wastewater under growth supportive condition. Transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDXS) suggest the presence of Cd in the cells from mid-stationary phase. The cell fractionation study revealed membrane and periplasm to be the major accumulating site in this strain. The chemical nature of the accumulated Cd was studied by X-ray powder diffraction analysis.